The PENYIAPAN KAMAR TAMU DI THE EXCELTON HOTEL PALEMBANG - Nova, Lovia; Pratiyudha, Dilla; Permatasari, Mustika; Ariasri, Nyoman Reni (Journal of Hospitality Accommodation Management (JHAM), 2025)
Room attendants are floor section officers responsible for maintaining the cleanliness, order, comfort, and completeness of guest rooms. However, some guest reviews indicate their dissatisfaction with the cleanliness of the room. The study, therefore, aims to investigate how the room attendants prepare the guest’s room. The author uses a descriptive qualitative research method. Data collection includes interviews, observation, documentation, and literature study. The findings show that there are 3 (three) steps in SOP (standard operating procedure) that are not implemented properly by room attendants, namely checking the minibar first and checking other equipment in the room, such as ashtrays, remote controls, and towels. The situation worsens when the hotel occupation is high. Further studies need to be conducted on the ideal number of room attendants during the high seasons.